Memaknai Ritual Seba Baduy untuk Pariwisata: Bagaimana Budaya Diterjemahkan Ke Wisatawan - Hardiman Hardiman; Arina Nindyar Saraswati; Zam Zam Masrurun; Atika Nur Hidayah (Yayasan Literasi Sains Indonesia, 2025)
paragraph Cultural tourism is increasingly in demand by tourists looking for authentic and transformative experiences. One of the traditions that has great potential is the Seba Baduy ritual, which is an annual procession of the Baduy people that contains spiritual, social, and ecological values. This research aims to interpret the symbolism in the Seba Baduy ritual and analyze how the culture is translated and perceived by tourists. This study uses a qualitative descriptive design, data collection is carried out by means of observation, interviews, documentation and observational literature studies, in-depth interviews, and literature analysis. The results of the study show that attributes in rituals, such as traditional clothing, travel procedures, and offering processions, are seen as representations of harmony between humans, nature, and ancestors. Tourists interpret this ritual as an authentic cultural experience, which not only offers tourist attractions but also provides a new understanding of local wisdom. In conclusion, Seba Baduy can play a role as a model for the development of cultural tourism that not only provides economic benefits, but also maintains the preservation of customary values. The implication of this research is the importance of collaboration between local communities, governments, and tourism actors to create sustainable promotion and management strategies.